2018
DOI: 10.18087/cardio.2018.8.10160
|View full text |Cite
|
Sign up to set email alerts
|

Fibrogenesis Genes and Susceptibility to Coronary Atherosclerosis

Abstract: Роль генов фиброгенеза в формировании подверженности к коронарному атеросклерозу Ключевые слова: атеросклероз коронарных артерий, ишемическая болезнь сердца, инфаркт миокарда, полиморфизм генов ADAMDEC1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Of crucial importance, the current study obtained evidence verifying the existence of low expression of CDKN2B-AS1 in clinical atherosclerotic plaque tissues, while elucidating the potential anti-atherogenic role of CDKN2B-AS1. In line with our study, it has been reported that the susceptibility to coronary atherosclerosis and the prognosis of disease progression involve extracellular matrix metabolism and fibrogenesis whereby CDKN2B-AS1 assumes an essential role [27]. Additionally, the results of the current study also indicated that ADAM10 was highly expressed in atherosclerotic plaque tissues and ox-LDL-exposed THP-1 macrophages.…”
Section: Discussionsupporting
confidence: 90%
“…Of crucial importance, the current study obtained evidence verifying the existence of low expression of CDKN2B-AS1 in clinical atherosclerotic plaque tissues, while elucidating the potential anti-atherogenic role of CDKN2B-AS1. In line with our study, it has been reported that the susceptibility to coronary atherosclerosis and the prognosis of disease progression involve extracellular matrix metabolism and fibrogenesis whereby CDKN2B-AS1 assumes an essential role [27]. Additionally, the results of the current study also indicated that ADAM10 was highly expressed in atherosclerotic plaque tissues and ox-LDL-exposed THP-1 macrophages.…”
Section: Discussionsupporting
confidence: 90%